2006
DOI: 10.1590/s0100-204x2006000400013
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização da comunidade bacteriana endofítica de citros por isolamento, PCR específico e DGGE

Abstract: Resumo -O objetivo deste trabalho foi caracterizar a comunidade bacteriana endofítica de plantas assintomáticas (escapes) e afetadas pela clorose variegada dos citros (CVC) por meio de isolamento em meio de cultura, técnica de gradiente desnaturante em gel de eletroforese (DGGE) e detecção de Methylobacterium mesophilicum e Xyllela fastidiosa por meio de PCR específico, para estudar esta comunidade e sua relação com a ocorrência da CVC. A análise da comunidade bacteriana via DGGE permitiu a detecção de X. fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
15

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 17 publications
(12 reference statements)
0
5
0
15
Order By: Relevance
“…Furthermore, the frequency of endophytic bacteria in healthy, escape, and CVC-affected Citrus sinensis plants was studied using cultivation as well as cultivation-independent methods (Araújo et al ., 2002). Bacteria from the genus Methylobacterium were the most frequently isolated endophytes from CVC-symptomatic citrus plants ( C. sinensis ) (Araújo et al ., 2002; Lacava et al ., 2004, 2006a,b); however, Araújo et al . (2002) observed that M. extorquens was only isolated from CVC-affected plants while M. mesophilicum was isolated from healthy plants, indicating that specific Methylobacterium species may be related to the citrus plant physiological condition.…”
Section: Endophytic Bacteria From Citrus Plants and Interactions Withmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, the frequency of endophytic bacteria in healthy, escape, and CVC-affected Citrus sinensis plants was studied using cultivation as well as cultivation-independent methods (Araújo et al ., 2002). Bacteria from the genus Methylobacterium were the most frequently isolated endophytes from CVC-symptomatic citrus plants ( C. sinensis ) (Araújo et al ., 2002; Lacava et al ., 2004, 2006a,b); however, Araújo et al . (2002) observed that M. extorquens was only isolated from CVC-affected plants while M. mesophilicum was isolated from healthy plants, indicating that specific Methylobacterium species may be related to the citrus plant physiological condition.…”
Section: Endophytic Bacteria From Citrus Plants and Interactions Withmentioning
confidence: 97%
“…Several reports highlighted the relationships among bacterial populations and suggest that CVC symptoms in citrus plants could be influenced by the population balance among Methylobacterium spp., Curtobacterium flaccumfaciens and X. fastidiosa (Araújo et al ., 2002; Lacava et al ., 2004, 2006b, 2007a; Ferreira Filho et al ., 2012). Understanding the relationship among endophytic bacteria within sweet orange trees and X. fastidiosa may lead to strategies to control CVC using endophytic bacteria (Ferreira Filho et al ., 2012) or inducing physiological shifts in both the host plant and microbial community that result in more balanced and stable interactions.…”
Section: Endophytic Microorganisms and Biological Controlmentioning
confidence: 99%
“…The genus Methylobacterium, which occupies the same ecological niche as Xfp, was the most frequently isolated endophytic bacterium from CVC-symptomatic citrus plants (Citrus sinensis) (Araújo et al, 2002;Lacava et al, 2004Lacava et al, , 2006aLacava et al, , 2006b. Recently, an interaction between Methylobacterium species and Xfp was strongly indicated (Araújo et al, 2002;Lacava et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Its positive activity was also reported in an assay for growth enhancement in plants (Sessitsch et al, 2004). Lacava et al (2006) characterized the endophytic bacterial community of citrus and investigated its relationship with the occurrence of citrus variegated chlorosis (CVC). In asymptomatic plants, the endophyte community has been reported to be composed of the genera Klebsiella sp, Acinetobacter sp, Curtobacterium sp, Pseudomonas sp, Enterobacter sp, Bacillus spp, and Methylobacterium mesophilicum, whereas CVC-affected plants are preferential hosts of Methylobacterium spp.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, Arnold and Herre (2003) noted that these factors affect the occurrence of endophytes. After isolation, many endophytes could not be cultivated, perhaps due to their need of culture media or specific conditions for growth (Lacava et al, 2006).…”
Section: Discussionmentioning
confidence: 99%